Respuestas
Respuesta dada por:
22
Buenas...
Lo que se pide es despejar t y asumiendo que ese dos es un exponente
Entonces..
![s=\frac{1}{2} *g*t^{2}
(2s)/g=t^2
t= \sqrt{ \frac{2s}{g} } s=\frac{1}{2} *g*t^{2}
(2s)/g=t^2
t= \sqrt{ \frac{2s}{g} }](https://tex.z-dn.net/?f=s%3D%5Cfrac%7B1%7D%7B2%7D+%2Ag%2At%5E%7B2%7D+%0A%0A%282s%29%2Fg%3Dt%5E2%0A%0At%3D+%5Csqrt%7B+%5Cfrac%7B2s%7D%7Bg%7D+%7D+)
Eso sería todo.
Lo que se pide es despejar t y asumiendo que ese dos es un exponente
Entonces..
Eso sería todo.
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años